(untitled) (International Journal of Food and Nutritional Sciences, 2024)
India has come a long way since its policy on economic liberalization and has now become one of the fastest growing economies in the world. This feat of India has been largely because of its prominence in the international stage in different realms and one such important sector is Tourism. This country is famous for its rich cultural heritage, diverse geographical locations, exotic sites, historical landmarks, mouthwatering cuisine and a nurturing environment creating a potential hub for both national and international tourists. The G20 provides a platform where India can make its internal tourism environment known to the delegates of all the remaining nations. The GOI has also adopted certain strategies to leverage this opportunity. The present paper is an attempt to highlight the government initiatives to boost the tourism sector along with analyzing the impact of its G20 leadership on its tourism sector. The study found that the fund allocation to different schemes intended to upgrade this sector has shown an upward trend on a yearly basis. FY 2023-24 has a total budget allocation in tourism of Rs 2400crores which is 78.69% more than the previous year. However on analyzing the present status of tourism in India, it is seen that although there has been an increase in the number of tourist influx and the amount of FEEs earned in 2023 during the period of Jan- Sept, but on comparing it with the same period in 2022, it can be concluded that its performance has not been satisfactory.